2012
DOI: 10.3821/145.4.cpj174
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Teaching Physical Examination to Pharmacists

Abstract: Prior to the session, most participants did not use PE in their practice, primarily due to a lack of formal training. The session significantly improved participants' confidence in PE, but this did not translate into short-term practice change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
(4 reference statements)
2
8
0
Order By: Relevance
“…In this study, some pharmacists stated that it is not part of their job role as independent prescribers, whilst others said they were not competent and comfortable undertaking this. This is consistent with previous work on pharmacists in Canada who reported that they were uncomfortable performing physical examinations on patients (42.9% of a sample of 28 pharmacists) or believed they do not need to perform physical examinations as they have access to this information from examinations conducted by other healthcare professionals (32.1%) (Barry, Mccarthy, Nelson, & Pearson, ).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, some pharmacists stated that it is not part of their job role as independent prescribers, whilst others said they were not competent and comfortable undertaking this. This is consistent with previous work on pharmacists in Canada who reported that they were uncomfortable performing physical examinations on patients (42.9% of a sample of 28 pharmacists) or believed they do not need to perform physical examinations as they have access to this information from examinations conducted by other healthcare professionals (32.1%) (Barry, Mccarthy, Nelson, & Pearson, ).…”
Section: Discussionsupporting
confidence: 89%
“…In this respect, there appears to be some similarity with a review of studies of learning transfer, which found that the effectiveness of training in changing practice behaviours was estimated at being between 10% and 40% (Burke & Hutchins, ). However, as patient‐centred consultation has been shown to have a positive effect on patients’ health behaviours and outcomes (Dwamena et al., ), it is encouraging to note that all the domains were correlated with this target behaviour, suggesting that the training had in particular contributed to this behaviour being implemented in practice; conversely, that weaker associations were seen between the TDF domains ‘skills’, ‘knowledge’, ‘beliefs in abilities’ and the physical examination target behaviour suggests the training intervention could go further in developing physical examination skills, in common with a previous study that found limited training transfer of physical examination skills to practice among pharmacists (Barry, McCarthy, Nelson, & Pearson, ). Whether this limited transfer to practice is explained by pharmacists’ identifying themselves primarily as medicines‐experts or with patients’ perceptions of pharmacists as medicines‐advisors has yet to be determined Luetsch, ; Eades et al., ).…”
Section: Discussionsupporting
confidence: 66%
“…In a study by Barry et al, which evaluated pharmacist’s perceptions of providing physical exams, they found that the three most common barriers to providing physical assessment identified by pharmacists were: feeling uncomfortable performing physical exams, lack of training, and a perceived impression that patients would be uncomfortable with a pharmacist completing this type of intervention [ 24 ]. In a second study, by Breault, et al, which assessed licensed pharmacist’s impressions of physical assessment skills in an institutional setting before and after a workshop, the most common barriers identified as to why physical assessment is not performed in practice were: lack of comfort, lack of training, and deeming it unnecessary since other professionals complete this skill [ 24 ]. Additionally, when pharmacists scored their level of comfort before the workshop, the average score was a one, which translated to “not confident” in performing physical assessments [ 25 ].…”
Section: Discussionmentioning
confidence: 99%